The Nexus Between Islamic Bank Financing for MSMEs, Financing Quality, and Regional Unemployment: Evidence from Indonesian Provinces - Mutia Pamikatsih; Purwanto (Yayasan Darussalam Bengkulu, 2026)
Background: As the stability of the labor market becomes a central pillar of regional economic resilience, the role of Islamic financial intermediation faces critical scrutiny. While Islamic banking aims to foster social welfare, the transmission gap between financing expansion and actual employment absorption remains a challenge. This study investigates the nexus between Islamic MSME financing, financing quality, and regional unemployment across 33 Indonesian provinces, evaluating whether the quality of intermediation (risk) or its quantity (volume) serves as the primary determinant for labor market outcomes. Method: Utilizing a balanced panel data set of 198 observations from 2020 to 2025, this research employs a quantitative approach. The analytical framework utilizes the Fixed Effect Model (FEM) with Robust Standard Errors (Huber-White sandwich estimators) to address heteroskedasticity and first-order autocorrelation. The model was validated through the Chow, Hausman, Modified Wald, and Wooldridge tests to ensure the robustness of the empirical findings. Results: The empirical results reveal that Non-Performing Financing (NPF) exerts a significant positive impact on the unemployment rate (p < 0.05), confirming that elevated credit risk triggers business failures and subsequent job losses. Conversely, MSME financing volume and liquidity ratios (FDR) exhibit no significant direct effect on unemployment reduction. Notably, economic growth (GRDP) remains the primary negative predictor of unemployment, reaffirming the validity of Okun’s Law in the regional context. Conclusion: This study concludes that the quality of Islamic banking intermediation is more critical than its quantity in addressing socio-economic challenges. Strengthening risk management and financing quality is essential to prevent a credit crunch that hinders labor absorption. Policy interventions should shift from purely growth-oriented strategies to risk-managed growth, ensuring that financing is directed toward labor-intensive sectors accompanied by robust business mentorship to safeguard regional employment stability.